Pro-environmental behaviors through the lens of the theory of planned behavior: A scoping review - Yuriev, Alexander; Dahmen, Mehdi; Paillé, Pascal; Boiral, Olivier; Guillaumie, Laurence (Resources, conservation and recycling, 2020)
•The TPB was used to explore numerous conservation behaviors.•Scholars tend to overlook mediating variables when predicting green behaviors.•Additional variables consistently increase the predictive power of the theory.•A roadmap provides useful guidance to scholars that intend to apply the TPB. The theory of planned behavior (TPB) allows researchers to identify the determinants of environmental behavior and subsequently target these factors in interventions. Multiple studies on conservation behaviors have recently applied this theoretical framework in both organizational and domestic settings. To shed more light on how the TPB was used in these studies, we conducted a literature review with the following objectives: 1) explore which individual green behaviors were studied though the lens of the TPB, 2) understand how scholars have used the theory and what variance the theory has helped to explain, and 3) formulate recommendations, if necessary, for improving the use of the theory. The review of the results from 126 publications demonstrated that the majority of scholars tend to overlook the importance of identifying and evaluating indirect variables (beliefs) that affect behaviors. More than half of the analyzed articles did not report the amount of explained variance, which undermines the principal strength of the theory. Scholars could obtain more substantial and consistent results if the guidelines regarding the application of the theory are consistently respected. More specifically, four aspects should be considered in the application of the theory: choice of framework, decision to extend the original model, methodology, and results. To help scholars overcome these commonly encountered problems, this article suggests a roadmap with several guiding questions and possible answers.